1996
DOI: 10.1056/nejm199602083340606
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Academic Institutions and Industry in the Life Sciences — An Industry Survey

Abstract: After more than a decade of sustained interaction, universities and industries seem to have formed durable partnerships in the life sciences, although the relationships may pose greater threats to the openness of scientific communication than universities generally acknowledge. However, industrial support for university research is much smaller in amount than federal support, and companies are unlikely to be able to compensate for sizable federal cutbacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
140
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(150 citation statements)
references
References 8 publications
5
140
0
5
Order By: Relevance
“…Disadvantages may be caused either by slow decision-making on part of TTOs, which may be hazardous in patent racing research, or may be caused by the firm being called upon to inform these procedures in conflict with its concern for confidential aspects of its knowledge and expectations. 3) Finally, research is difficult to contract on, not least because a spe-5 These terms corresponds well the typical set-up for industry sponsorship of academic life-science research as identified in more comprehensive surveys, when we correct for their inclusion also of more short-term research issues (Blumenthal et al 1996) 6 Lagen om rätten till arbetstagares uppfinningar, LAU 1949:345. This specific exception to employer's ownership to their inventions is currently under consideration for reform See e.g.…”
Section: Lup and Its Implicationsmentioning
confidence: 99%
“…Disadvantages may be caused either by slow decision-making on part of TTOs, which may be hazardous in patent racing research, or may be caused by the firm being called upon to inform these procedures in conflict with its concern for confidential aspects of its knowledge and expectations. 3) Finally, research is difficult to contract on, not least because a spe-5 These terms corresponds well the typical set-up for industry sponsorship of academic life-science research as identified in more comprehensive surveys, when we correct for their inclusion also of more short-term research issues (Blumenthal et al 1996) 6 Lagen om rätten till arbetstagares uppfinningar, LAU 1949:345. This specific exception to employer's ownership to their inventions is currently under consideration for reform See e.g.…”
Section: Lup and Its Implicationsmentioning
confidence: 99%
“…On one hand, surveys of academic scientists have found that patenting skews scientists' research agendas toward commercial priorities, causes delay in the public dissemination of research findings, and crowds out effort devoted to producing public research (Blumenthal et al, 1996;Campbell et al 2002;Krimsky, 2003). In stark terms, this work has portrayed a tradeoff between patenting and the progress of academic science.…”
Section: Introductionmentioning
confidence: 99%
“…The rationalization of resources force us to know what the outcomes of medical actions are. For this reason, measurement methods have been developed to quantify and thus improve the quality of our healthcare services [6][7][8], where the patients' subjective perception of wellbeing after completing the treatment is increasingly important [17].…”
Section: Introductionmentioning
confidence: 99%